A two-dimensional Bi 2 WO 6 -Ti 3 C 2 Tx-mg-C 3 N 4 Preparation method and application of ternary composite catalyst
Ti3C2Tx MXene was prepared by template method and combined with Bi2WO6, and a two-dimensional Bi2WO6-Ti3C2Tx-mg-C3N4 ternary composite catalyst was prepared by hydrothermal method, which solved the problem of difficult to efficiently degrade blood lipid pollutants in the prior art, and achieved a degradation effect with low cost, high activity and stable performance.
Patent Information
- Application Number
- CN202411755933.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-03
AI Technical Summary
The prior art is difficult to efficiently degrade blood lipid-lowering pollutants in water environments, and is costly, low in activity and unstable in performance.
Mesoporous mg-C3N4 was prepared by template method, and Ti3AlC2 was etched by HCl and LiF to obtain Ti3C2Tx MXene, combined with Bi(NO3)3•5H2O and Na2WO4•2H2O, and a two-dimensional Bi2WO6-Ti3C2Tx-mg-C3N4 ternary composite catalyst was prepared by hydrothermal method.
It has achieved efficient degradation of blood lipid-lowering pollutants in water environments, and has the advantages of low cost, high activity and stable performance.
Smart Images

Figure CN119215960B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of photocatalyst preparation, and in particular to a preparation method and application of a two-dimensional Bi2WO6-Ti3C2Tx-mg-C3N4 ternary composite catalyst. Background Art
[0002] Among the numerous refined green process technologies, light energy utilization-related technologies are one of the development directions for efficient degradation of pollutants and low-carbonization of sewage treatment. Among them, photocatalytic technology is widely used in the degradation research of complex organic pollutants, and more than 95% of organic matter can be decomposed by photocatalytic oxidation. Therefore, the technology of selective degradation of lipid-lowering drugs using solar energy photocatalysis under mild conditions has become one of the effective ways to efficiently degrade difficult-to-degrade pollutants.
[0003] In fact, the regulation of energy bands and morphology of semiconductor photocatalysts is closely related to photocatalytic performance. In the past two decades, in order to improve the photocatalytic performance of heterojunction composite semiconductors, researchers have developed a series of energy band regulation strategies such as pn-type heterojunction, Z-Scheme (Z-type) heterojunction and semiconductor-carbon material heterojunction. The research group of W. Jo, S. Kumar, S. Eslava, S. Tonda has successively reported Bi2WO6 / RGO / g-C3N4 and CoAl-LDH / g-C3N4 / RGO 2D / 2D / 2D heterostructures, which are used for efficient photoreduction of solar fuels and degradation of dyes and antibiotics, respectively; the 2D structure acts as a bridge with high charge conductivity, generates a built-in electric field, gathers interface electrons, and greatly shortens the charge transfer distance between semiconductors. The inventor's team previously prepared and synthesized the Bi / Bi2WO6 / mg-C3N4 heterojunction composite catalyst in the "Construction of g-C3N4-based photocatalytic system and study of its visible light catalytic degradation efficiency and mechanism of BZF" and explored its removal efficiency for lipid-lowering drugs. The analysis showed that the photocatalytic mechanism of the system is: in the area where the heterostructure is formed, metal Bi acts as a bridge for electron transmission, promoting the transfer of Bi2WO6 conduction band e- to mg-C3N4 valence band, forming a Z-type carrier transport mechanism, thereby inhibiting carrier recombination. However, compared with zero-dimensional (0D) metallic Bi, two-dimensional (2D) layered MXene has ultra-high electron transport capacity. If the performance advantages of 2D MXene can be combined, and a 2D structural layer is introduced into the Bi2WO6 / mg-C3N4 structure to form a 2D / 2D / 2DBi2WO6-Ti3C2Tx-mg-C3N4 heterostructure (MXene-based photocatalytic system), then the closely contacted 2D / 2D / 2D heterojunction can greatly improve the carrier transfer and photoinduced electron separation rate at the heterojunction interface due to the strong interfacial electron coupling effect. The rationally designed layered surface activated 2D / 2D / 2D MXene-based photocatalytic system with a specific adsorption-catalytic structure and enhanced light absorption performance (unique layered structure is conducive to improving quantum yield) will more efficiently promote the generation of ROSs. At the same time, ROSs, as a bridge between the MXene-based photocatalytic system and the degradation of lipid-lowering drugs, are more conducive to the controllable degradation of lipid-lowering drugs.
[0004] The Chinese patent with the authorization announcement number CN 105148974 B discloses a highly active mpg-C3N4 / REBiVO4 heterojunction photocatalyst and its preparation method and application. First, mpg-C3N4 powder is prepared and dispersed in ethanol; then bismuth nitrate pentahydrate solution is mixed with ammonium metavanadate solution and its pH value is adjusted, and then rare earth nitrate is added to obtain a precursor RE-BiVO4 suspension; then the mpg-C3N4 alcohol solution is added to the precursor RE-BiVO4 suspension to obtain a reaction precursor solution, and finally the mpg-C3N4 / RE-BiVO4 heterojunction photocatalyst is prepared by microwave hydrothermal method. The catalyst is a heterojunction structure formed by mesoporous mpg-C3N4 and rod-shaped tetragonal zircon phase RE-BiVO4, has high photocatalytic activity under simulated sunlight irradiation, greatly improves the photocatalytic efficiency of pure phase BiVO4, and has good application prospects in the treatment of environmental pollutants. The disadvantage of the above preparation method is that the preparation method uses rare earth elements (such as Nd and Er) for doping, which increases the cost and complexity of the material.
[0005] Therefore, it has become an inevitable trend of technological development to further develop a method for preparing a two-dimensional Bi2WO6-Ti3C2Tx-mg-C3N4 ternary composite catalyst that can efficiently degrade lipid-lowering pollutants in water environments and has low cost, high activity and stable performance, and to apply it. Summary of the invention
[0006] The technical problem to be solved by the present invention is to provide a preparation method and application of a two-dimensional Bi2WO6-Ti3C2Tx-mg-C3N4 ternary composite catalyst, in order to efficiently degrade lipid-lowering pollutants in the water environment.
[0007] In order to solve the above technical problems, the technical solutions adopted by the present invention are as follows:
[0008] A method for preparing a two-dimensional Bi2WO6-Ti3C2Tx-mg-C3N4 ternary composite catalyst comprises the following steps:
[0009] a. Preparation of mesoporous mg-C3N4, synthesizing a g-C3N4 precursor on the surface of a mesoporous SiO2 ball by a template method, removing the template by NH5F corrosion, and obtaining mesoporous mg-C3N4, wherein the mesoporous mg-C3N4 refers to g-C3N4 having a mesoporous structure prepared by a template method;
[0010] b. Preparation of Ti3C2Tx, etching Ti3AlC2 with HCl and LiF to obtain Ti3C2Tx MXene;
[0011] c. Prepare a two-dimensional Bi2WO6-Ti3C2Tx-mg-C3N4 ternary composite catalyst, use Bi(NO3)3•5H2O as the Bi source and Na2WO4•2H2O as the W source, anchor mg-C3N4 and Ti3C2Tx into the Bi2WO6 precursor solution, and prepare a two-dimensional Bi2WO6-Ti3C2Tx-mg-C3N4 ternary composite catalyst by hydrothermal method.
[0012] Further optimized, the specific preparation method of the mesoporous mg-C3N4 is:
[0013] a. Dissolve urea in a silica gel solution, wherein the silica gel solution is 12 nm SiO2 LudoxHS40 with a mass concentration of 40%, and heat in a constant temperature water bath at 70-90°C until solidified;
[0014] b. Grind the solidified sample and transfer it to a sample boat, and perform high-temperature heat treatment in a tube furnace under nitrogen protection;
[0015] c. Grind the powder at room temperature and place it in a 2-6 mol / L NH5F solution for ultrasonic treatment for 6-12 hours to remove the template Si in the g-C3N4 precursor;
[0016] d. After the ultrasonic treatment is completed, filter, wash and dry to obtain mesoporous mg-C3N4.
[0017] Further optimized, the mass ratio of urea to silica gel solution is 1:6-1:10, the heating rate of the tubular furnace is 2-5°C / min, and the high-temperature heat treatment reaction time is 3-6 hours.
[0018] Further optimized, the specific preparation method of Ti3C2Tx is:
[0019] a. Ti3AlC2 was added to a mixed solution of HCl and LiF in a molar ratio of 1:2:1-1:1:1 and stirred at room temperature for 8 hours;
[0020] b. Wash with dilute hydrochloric acid and ultrapure water several times and dry to remove other free ions on the surface of Ti3C2, improve the purity of the product, and obtain Ti3C2;
[0021] c. Under nitrogen protection, the prepared Ti3C2 was ultrasonically dispersed into DMF, 100-200mL DMF was added per gram of Ti3C2, and the ultrasonic treatment time was 6-8 hours to obtain a suspension;
[0022] d. After the suspension is processed, centrifuge, wash and dry;
[0023] e. The dried sample was dispersed in deionized water and continued to be ultrasonically treated for 1-2 hours under nitrogen protection to obtain Ti3C2Tx MXene nanosheets.
[0024] Further optimized, the flow rate of nitrogen protection during the ultrasonic treatment is 200 mL / min.
[0025] Further optimized, the molar ratio of Bi(NO3)3•5H2O to Na2WO4•2H2O is 2:1, and the mass ratio of the theoretical calculated amount of Bi2WO6 in mg-C3N4 and Ti3C2Tx to the Bi2WO6 precursor solution is 5:1:10-1:1:20; the two-dimensional Bi2WO6-Ti3C2Tx-mg-C3N4 ternary composite catalyst prepared by hydrothermal reaction is specifically prepared at a reaction temperature of 160-200°C for 6-8 hours to prepare the two-dimensional Bi2WO6-Ti3C2Tx-mg-C3N4 ternary composite catalyst.
[0026] The two-dimensional Bi2WO6-Ti3C2Tx-mg-C3N4 ternary composite catalyst prepared by the preparation method of the present invention is used in degrading lipid-lowering pollutants in water environments.
[0027] The beneficial effects of the above technical solution are as follows: in the region where the heterostructure is formed, the metal Bi acts as a bridge for electron transmission, promoting the transfer of the Bi2WO6 conduction band e- to the mg-C3N4 valence band, forming a Z-type carrier transport mechanism, thereby inhibiting the recombination of carriers; compared with zero-dimensional (0D) metal Bi, the two-dimensional (2D) layered MXene has an ultra-high electron transport capacity. Combined with the performance advantages of 2D MXene, a 2D structural layer is introduced into the Bi2WO6 / mg-C3N4 structure to form a 2D / 2D / 2D Bi2WO6-Ti3C2Tx-mg-C3N4 heterostructure (MXene-based photocatalytic system). The closely contacted 2D / 2D / 2D heterojunction has a strong interface electron coupling effect, which greatly improves the carrier transfer and photoinduced electron separation rate at the heterojunction interface; after a reasonable design of layered surface activated 2D / 2D / 2D The MXene-based photocatalytic system has a specific adsorption-catalytic structure and enhanced light absorption performance (the unique layered structure is conducive to improving the quantum yield) and will more efficiently promote the generation of ROSs; at the same time, ROSs, as a bridge connecting the MXene-based photocatalytic system and the degradation of lipid-lowering drugs, is more conducive to the controllable degradation of lipid-lowering drugs. Therefore, the present invention can efficiently degrade lipid-lowering pollutants in the water environment; the present invention also has the advantages of low cost, high activity and stable performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1TEM image of the two-dimensional Bi2WO6-Ti3C2Tx-mg-C3N4 ternary composite catalyst;
[0029] Figure 2 HRTEM image of the two-dimensional Bi2WO6-Ti3C2Tx-mg-C3N4 ternary composite catalyst;
[0030] Figure 3 This is a schematic diagram of the activity evaluation of BZF degradation by simulated sunlight according to the present invention;
[0031] Figure 4 Schematic diagram of the stability evaluation of Bi2WO6-Ti3C2Tx-mg-C3N4 heterojunction composite photocatalyst. DETAILED DESCRIPTION
[0032] The following examples describe the present invention in detail. In the description of the following examples, specific details such as specific system structures, technologies, etc. are proposed for illustration rather than for limitation, so as to thoroughly understand the present application embodiments. However, it should be clear to those skilled in the art that the present application can also be implemented in other embodiments without these specific details. In other cases, the detailed description of well-known systems, devices, circuits and methods is omitted to prevent unnecessary details from hindering the description of the present application. It should be understood that when used in the present application specification and the attached claims, the term "comprising" indicates the presence of the described features, wholes, steps, operations, elements and / or components, but does not exclude the presence or addition of one or more other features, wholes, steps, operations, elements, components and / or their collections. It should also be understood that the term "and / or" used in the present application specification and the attached claims refers to any combination of one or more of the items listed in association and all possible combinations, and includes these combinations.
[0033] In addition, in the description of the present application specification and the attached claims, the terms "first", "second", "third", etc. are only used to distinguish the description and cannot be understood as indicating or implying relative importance. The reference to "one embodiment" or "some embodiments" described in the present application specification means that one or more embodiments of the present application include specific features, structures or characteristics described in conjunction with the embodiment. Therefore, the statements "in one embodiment", "in some embodiments", "in some other embodiments", "in some other embodiments", etc. that appear in the different parts of this specification do not necessarily refer to the same embodiment, but mean "one or more but not all embodiments", unless otherwise specifically emphasized in other ways. The terms "including", "comprising", "having" and their variations all mean "including but not limited to", unless otherwise specifically emphasized in other ways. Example 1
[0034] (1) Preparation of mesoporous mg-C3N4
[0035] First, 6 g of urea was dissolved in 50 g of silica gel solution and heated in a constant temperature water bath at 90 °C under magnetic stirring until the water was completely evaporated. The obtained solid was then ground and transferred to a sample boat. Under the protection of a nitrogen flow rate of 250 mL / min, the temperature was raised to 530 °C at 3 °C / min in a tube furnace and heat treated for 5 h. After the treatment, the solution was taken out at room temperature and ground again. The powder was placed in 20 mL of 5 mol / L NH5F solution and ultrasonically treated for 8 h to remove the template Si in the g-C3N4 precursor. After the ultrasonic treatment, the solution was centrifuged and filtered, washed three times with deionized water and anhydrous ethanol respectively, and dried at 80 °C for 8 h to obtain mesoporous g-C3N4.
[0036] (2) Preparation of Ti3C2Tx
[0037] First, 6.227 g Ti3AlC2 was added to a mixed solution of 40 mL 12 mol / L concentrated HCl and 3.328 g LiF, stirred at room temperature for 8 h, and after Al was etched away, it was washed with dilute hydrochloric acid and ultrapure water several times, and dried at 80 ° C to obtain Ti3C2. Under nitrogen protection, the prepared Ti3C2 was dispersed in 100 mL DMF (N, N-dimethylacetamide). After 6.227 g Ti3AlC2 was etched away Al, approximately 5.363 g Ti3C2 could be prepared, which is equivalent to 100 mL / 5.363 = 18.65 mL DMF per gram of Ti3C2. Ultrasonic treatment was performed for 8 h. After completion, the suspension was centrifuged, washed, and dried at 80 ° C. Then 1 g of the dried sample was dispersed in 100 mL of deionized water and ultrasonically treated for 8 h under a nitrogen atmosphere. The obtained product was centrifuged, washed three times with deionized water and anhydrous ethanol respectively, and dried at 80 °C for 8 h to obtain Ti3C2Tx MXene nanosheets.
[0038] (3) Preparation of 2D / 2D / 2D Bi2WO6-Ti3C2Tx-mg-C3N4
[0039] 2.082 g Bi(NO3)3•5H2O and 0.708 g Na2WO4•2H2O were dispersed and dissolved in 120 mL deionized water to form a Bi2WO6 precursor solution, 0.5 g mg-C3N4 and 0.1 g Ti3C2Tx were dispersed in the Bi2WO6 precursor solution and ultrasonically treated for 2 h. The above mixture was transferred to a 150 mL reactor at 200 ° C for 6 h, cooled to room temperature, taken out and centrifuged, washed for no less than 3 times, and dried at 80 ° C for 8 h to prepare a 2D / 2D / 2D Bi2WO6-Ti3C2Tx-mg-C3N4 heterojunction composite photocatalyst.
[0040] The prepared 2D / 2D / 2D Bi2WO6-Ti3C2Tx-mg-C3N4 heterojunction composite photocatalyst was analyzed by transmission electron microscopy (TEM), and the results are shown in Figure 1. From the figure, the distribution of the three components of Bi2WO6, Ti3C2Tx and g-C3N4 in the composite catalyst can be clearly observed. Each component presents a certain microscopic morphology and is relatively evenly distributed, indicating that the various substances can be well compounded together during the preparation process. This uniform distribution is conducive to the interaction between the components and provides a good structural basis for the transmission of electrons and interface synergy in subsequent photocatalytic reactions.
[0041] Further high-resolution transmission electron microscopy (HRTEM) analysis of the 2D / 2D / 2D Bi2WO6-Ti3C2Tx-mg-C3N4 heterojunction composite photocatalyst revealed the following Figure 2 The results shown in the figure mark the lattice fringes of Bi2WO6 and Ti3C2Tx, and the lattice fringes spacing is 0.315nm and 1.248nm respectively. These lattice fringes spacing data accurately reflect the crystal structure characteristics of each component. By comparing with the known crystal structure data, the physical composition of Bi2WO6, Ti3C2Tx and g-C3N4 in the 2D / 2D / 2D Bi2WO6-Ti3C2Tx-mg-C3N4 heterojunction composite photocatalyst is further confirmed. Example 2
[0042] The two-dimensional Bi2WO6-Ti3C2Tx-mg-C3N4 ternary composite catalyst prepared by the above preparation method is used in the degradation of lipid-lowering pollutants in water environment. The photocatalytic experiment selected a CEL-LAB500 photochemical reaction device. In the experiment, a xenon lamp (power 300 W) was used as the light source, and a 290 nm filter was equipped to simulate sunlight. When conducting the photocatalytic activity test, 0.05 g of the 5:1:5 Bi2WO6-Ti3C2Tx-mg-C3N4 heterojunction composite photocatalyst obtained in Example 1 was added to 200 mL of a BZF reaction solution with a concentration of 5 mg / L, and the pH value was stabilized at about 6.0 with a phosphate buffer solution (0.1 mol / L, 5.0 mL). Figure 3 As shown in the figure, after 4 h of photocatalytic degradation reaction, the removal rate of BZF can reach up to 96.6%.
[0043] In the cycle stability test, the 5:1:5 Bi2WO6-Ti3C2Tx-mg-C3N4 heterojunction composite photocatalyst was cleaned after each cycle and finally dried under vacuum at 80 °C to ensure the consistency and reliability of its performance. Figure 4 As shown in the figure, after three cycles of experiments, the removal rate of BZF by the 5:1:5 Bi2WO6-Ti3C2Tx-mg-C3N4 heterojunction composite photocatalyst decreased to varying degrees, but the removal rate was still greater than 92%. Example 3
[0044] Evaluation of sunlight photocatalytic activity: A crystal dish with a diameter of 145 mm and a height of 70 mm was used as a photocatalytic reactor, and 0.05 g of 5:1:5 Bi2WO6-Ti3C2Tx-mg-C3N4 prepared in Example 1 was added to 200 mL of BZF simulated wastewater with a concentration of 3 mg / L. The rooftop without any obstructions was selected for the sunlight-driven photocatalytic degradation experiment. Before illumination, dark adsorption was carried out for 30 minutes in the dark, and sunlight irradiation was implemented after reaching the adsorption-desorption equilibrium. The irradiation time was 10:00-16:00 in early August in Shijiazhuang city when the weather was clear. After 6 h of photocatalytic reaction, the sample was taken, and the concentration of BZF before the reaction was 3 mg / L by liquid chromatography, and the concentration of BZF after the reaction was 0.14 mg / L. The calculated degradation rate was 95.4%.
[0045] The present invention can efficiently degrade lipid-lowering pollutants in water environments and has the advantages of low cost, high activity, stable performance, etc.
[0046] Finally, it should be noted that the above are only preferred embodiments of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein with equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the scope of protection of the claims of the present invention.
Claims
1. Application of a two-dimensional Bi2WO6-Ti3C2Tx-mg-C3N4 ternary composite catalyst in the degradation of BZF pollutants in water environment, the preparation method of the two-dimensional Bi2WO6-Ti3C2Tx-mg-C3N4 ternary composite catalyst comprising the following steps: a. Preparation of mesoporous mg-C3N4, synthesizing a g-C3N4 precursor on the surface of a mesoporous SiO2 ball by a template method, removing the template by NH5F corrosion, and obtaining mesoporous mg-C3N4, wherein the mesoporous mg-C3N4 refers to g-C3N4 having a mesoporous structure prepared by a template method; b. Preparation of Ti3C2Tx, etching Ti3AlC2 with HCl and LiF to obtain Ti3C2Tx MXene; c. Preparation of a two-dimensional Bi2WO6-Ti3C2Tx-mg-C3N4 ternary composite catalyst, using Bi(NO3)3•5H2O as the Bi source and Na2WO4•2H2O as the W source, anchoring mg-C3N4 and Ti3C2Tx into the Bi2WO6 precursor solution, and preparing a two-dimensional Bi2WO6-Ti3C2Tx-mg-C3N4 ternary composite catalyst by hydrothermal method; The specific preparation method of the mesoporous mg-C3N4 is: a. Dissolve urea in a silica gel solution and heat in a constant temperature water bath at 70-90°C until solidified. The silica gel solution is 12 nm SiO2 Ludox HS40 with a mass concentration of 40%; b. Grind the solidified sample and transfer it to a sample boat, and perform high-temperature heat treatment in a tube furnace under nitrogen protection; c. Grind the powder at room temperature and place it in a 2-6 mol / L NH5F solution for ultrasonic treatment for 6-12 hours to remove the template Si in the g-C3N4 precursor; d. After the ultrasonic treatment is completed, filtering, washing and drying are performed to obtain mesoporous mg-C3N4; The mass ratio of urea to silica gel solution is 1:6-1:10, the heating rate of the tubular furnace is 2-5°C / min, and the heat treatment reaction time at 520-540°C is 3-6 hours; The specific preparation method of Ti3C2Tx is: a. Add Ti3AlC2 to a mixed solution of HCl and LiF in a molar ratio of 1:2:1-1:1:1, and stir at room temperature until Al is etched away; b. Wash with dilute hydrochloric acid and ultrapure water several times and dry to remove other free ions on the surface of Ti3C2, improve the purity of the product, and obtain Ti3C2; c. Under nitrogen protection, the prepared Ti3C2 was ultrasonically dispersed into DMF, 100-200 mLDMF was added per gram of Ti3C2, and the ultrasonic treatment time was 6-8 hours to obtain a suspension; d. After the suspension is processed, centrifuge, wash and dry; e. The dried sample was dispersed in deionized water and ultrasonically treated for 1-2 hours under nitrogen protection to obtain Ti3C2Tx MXene nanosheets; The molar ratio of Bi(NO3)3•5H2O to Na2WO4•2H2O is 2:1, and the mass ratio of the theoretical calculated amount of Bi2WO6 in mg-C3N4 and Ti3C2Tx to the Bi2WO6 precursor solution is 5:1:10-1:1:20; the two-dimensional Bi2WO6-Ti3C2Tx-mg-C3N4 ternary composite catalyst is prepared by hydrothermal reaction at a reaction temperature of 160-200°C for 6-8 hours to prepare the two-dimensional Bi2WO6-Ti3C2Tx-mg-C3N4 ternary composite catalyst.
2. According to claim 1, the use of a two-dimensional Bi2WO6-Ti3C2Tx-mg-C3N4 ternary composite catalyst in the degradation of BZF pollutants in an aqueous environment, wherein the flow rate of nitrogen protection during ultrasonic treatment in the preparation step of the two-dimensional Bi2WO6-Ti3C2Tx-mg-C3N4 ternary composite catalyst is 200 mL / min.
Citation Information
Patent Citations
A high active mpg‑c 3 no 4 / re-bivo 4 Heterojunction photocatalyst and its preparation method and application
CN105148974B